Do processo penal democrático como fármaco para o processo penal pidiático - Suzuki, Claudio Mikio (2018)
Fear and hatred promote the legitimacy of an exception in criminal procedure. Such significant movements within the legal landscape are driven by public solidarity refusing potential impunity. Popular tactics include influence by the media and inflammatory, often viral, commentary made possible by present-day social networks. Criminal law and order becomes the solution to the perceived evils of postmodern society. The end of Brazil's military dictatorship gave birth to a society with newfound democratized information. Living in an exponentially expanding technological era, uncensored information is expansive and it is accessible. The foundation of criminal law is to fairly and democratically extirpate unlawful behavior along a continuum of actions including harmless violations as well as charges made against corrupt politicians -- a popular topic in these times. A free society has created a cultural idea of punishment argued to be fairer and just. This mindset may even, at times, move away from the established aims of the democratic criminal procedure. Free speech and uncensored news are positive concepts in any society. This is not under debate. Yet, when the popular cultural idea of justice begins to deviate from established law and order, problems occur. Ideas voiced at great marches in large urban centers, combined with social media explosions, can appear to contradict rules or laws of our country. Whether or not a difference exists between what society believes is unjust and what the courts deem unjust can become obscured. A faction of the population may emerge as "judge, jury, and executioner," to borrow a popular English expression. This may mark a return to vigilantism, a surge of individuals who believe the criminal law system is broken, and, therefore, undertake law and order without legal authority. In today's world, the term "vigilantes" can be easily substituted with "Facebook Judges". Working outside of the law, disorder can arise. The result can potentially be an outright uprising of the civilian population including civil and criminal disobedience. In a historical, comparative and bibliographical analysis, this work seeks the message coming from society as a whole and the current growth of the criminal law application, without observing the penal and penal procedural principles, for the punishment of these so-called enemies, and verify whether this current criminal policy represents an exercise in democracy or total disorder and defy